Pengaruh Museum Sampah Terhadap Keterampilan Kolaborasi Di Sekolah Dasar - muhammad fadil fadli; Rizal; Nurgan Tadeko (JURNAL DIKDAS, 2026)
Collaboration skills are one of the 21st-century skills that need to be developed from elementary school level. However, the implementation of learning that effectively trains students' collaboration skills is still not optimal. This study aims to determine the effect of using an Augmented Reality (AR)-based Waste Museum on the collaboration skills of elementary school students. This study used a quantitative approach with a One Group Pretest–Posttest type pre-experimental design. The subjects were 32 fifth-grade students of SD Inpres 3 Tondo in the 2025/2026 academic year. The data collection instrument was a collaboration skills questionnaire that had been validated by experts, supported by observation sheets and documentation. Data were analyzed using descriptive statistics, the Wilcoxon Signed Rank Test, and Rasch modeling to observe changes in individual student abilities and the quality of instrument items. The analysis results showed that the data were not normally distributed, so the Wilcoxon test was used. The Wilcoxon test results showed an increase in students' collaboration skills scores after participating in learning using the AR-based Waste Museum, although statistically the increase was not significant. However, the results of the effect size analysis indicated a learning effect in the small to moderate category. These findings indicate that the AR-based Waste Museum can create contextual, interactive, and meaningful learning experiences and has the potential to support the development of elementary school students' collaboration skills. Therefore, museum-based learning media and AR technology can be used as an innovative alternative for elementary school learning.